THE ROLE OF SOCIAL SERVICES AND BREAKFAST OF PEKANBARU CITY IN DEVELOPING PERSONS OF SOCIAL WELFARE PROBLEMS (PMKS) IN PEKANBARU CITY IN 2019 - Elvi Rahmi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Thesis writing entitled "The Role of the Pekanbaru City Social and Cemetery Service in Fostering Persons with Social Welfare Problems (PMKS) in Pekanbaru City in 2019". The causative factor for coaching Persons with Social Welfare Problems (PMKS) is the absence of facilities that support the development of Persons with Social Welfare Problems (PMKS) in Pekanbaru City. This research was conducted in Pekanbaru. The purpose of this study is to describe the role of the Pekanbaru City Social and Cemetery Service in the Development of Persons with Social Welfare Problems (PMKS) in Pekanbaru City in 2019. The theory used is the theory of guidance from Mathis. The research method used. The author is descriptive qualitative with data techniques, interviews and documentation. The type of data used by the author is primary data and secondary data. The result of this research is the lack of role of the Pekanbaru City Social and Cemetery Service in the Development of Persons with Social Welfare Problems (PMKS). Keywords: Role, Development, and Persons with Social Welfare Problems (PMKS)